VIRTUAL TRY-ON AND THE DIGITAL SHOPPING EXPERIENCE: A SYSTEMATIC LITERATURE REVIEW USING SCOPUS AI–ASSISTED ANALYSIS - Abas, Nurliyana; Hussin, Hanani; Mohammad, Azlyantiny; Rafie, Siti Khadijah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Virtual try-on (VTO), a fashion and appearance-based e-commerce category that largely consists of augmented reality (AR) and artificial intelligence (AI)-based applications, has become significant in improving online product evaluation. Although academic interest has grown, the available literature is still divided into technological, experiential, behavioural, and organisational views, which restricts a holistic view of how VTO generates value in online retail business contexts. This research is based on a systematic literature review of VTO publications, which are indexed by Scopus and were obtained on 13 February 2026. The search strategy was structured and implemented using titles, abstracts, and keywords, with concept mapping and thematic synthesis conducted through the help of AI. Five dominant thematic clusters are identified in the analysis and include technological innovation, consumer experience, behavioural responses, marketing and retail strategy, and e-commerce performance outcomes. Based on Stimulus-Organism-Response (S-O-R), this study formulates a conceptual framework that suggests that VTO technological features (stimulus) positively influence consumer experiential judgements (organism) which in turn positively impact organisational performance through behavioural responses (adoption and purchase intention). The study contributes to the literature as it brings together multidisciplinary results in a logical theoretical framework that connects the technological capability, psychological mechanisms, behavioural responses, and e-commerce performance outcomes. The results offer conceptual development and operational directions to retailers who wish to adopt immersive digital technologies in online retailing.